CAPTURING THE REALITY OF INDUSTRY 4.0 READINESS DIMENSIONS AND INDICATORS IN A DEVELOPING COUNTRY: AN ANALYSIS OF APPLYING I4.0 IN INDONESIA - Hasbullah, Hasbullah; Bareduan, Salleh Ahmad (The South African Journal of Industrial Engineering, 2023)
Indonesia has the lowest Industry 4.0 (I4.0) readiness in South East Asia, and uses the INDI 4.0 instrument (Indonesia Industry 4.0 readiness index), which is not as comprehensive and accurate as it could be. An Initial survey confirmed that only 56.86% of respondents agreed that INDI 4.0 accurately measured readiness in manufacturing operations. Unlike the primary I4.0 indices, INDI 4.0 lacks comprehensive I4.0 dimensions and characteristics. This paper aims to identify the dimensions and indicators of I4.0 readiness to enhance INDI 4.0 through an exploratory mixed-method research approach with a multiphase research design. The first phase consisted of a qualitative approach through a documentary review, interviews, and observations to explore the dimensions and indicators of I4.0 readiness. This phase successfully identified four dimensions that experts, academics, and practitioners validated: technology, data life cycle, I4.0 design principles, and smart factory. These dimensions were broken down into 27 indicators of I4.0 readiness, then validated again through a statistical approach before being affirmed by a survey with a Pearson’s correlation > 0.361 and Cronbach’s alpha of 0.987, which indicated validity and reliability. The second phase, using a quantitative approach through a survey, confirmed the four dimensions and 27 indicators for measuring I4.0 readiness levels; these were ‘not ready’, ‘early stage’, ‘moderate readiness’, ‘readiness ripe’, and ‘already implemented’. This finding comprehensively measured I4.0 readiness based on feedback from industries struggling to adopt I4.0, especially in developing countries such as Indonesia. This finding also differed from existing indices (Acatech, RAMI 4.0, Dreamy, SIMMI 4.0. IMPULS) from developed countries and industries already stable in implementing I4.0.